Gagasan kolonial tentang permasalahan lingkungan di Gresik pada paruh kedua abad XIX - Suryanullah, Ahmad Sholehuddin (Historiography: Journal of Indonesian History and Education, 2025)
Abstract This article describes colonial ideas about environmental problems in Gresik in the second half of the 19th century. The emergence of environmental issues in the first half of the 19th century, such as sedimentation, floods, and drought, made the Colonial Government look for alternatives to deal with these problems. Hence, efforts emerged to deal with environmental issues. This article was written using historical methods, namely topic selection, heuristics, criticism, interpretation, and historiography, and utilizing primary sources in the form of the Staatsblad, colonial verslag, Burgerlijke Openbare Werken (B.O.W.) verslag, and contemporary newspapers. This research shows that the emergence of the sedimentation problem in the Madura Strait is caused by colonial exploitation of forests in the upper reaches of the Bengawan Solo River as well as the problem of flood and drought cycles in Gresik, giving rise to an idea to overcome this problem. This idea was outlined in the plans carried out by Ledeboer and Pierson in the second half of the 19th century to build irrigation canals from Ngawi to Gresik to overcome sedimentation, flooding, and drought, resulting in the emergence of the largest irrigation project in the 19th century. 19, namely Solo Vallei Werken.Abstrak Tulisan ini menguraikan gagasan kolonial tentang permasalahan lingkungan di Gresik pada paruh kedua abad ke-19. Munculnya masalah-masalah lingkungan pada paruh pertama abad ke-19 seperti sedimentasi, banjir, dan kekeringan membuat Pemerintah Kolonial mencari alternatif untuk menangani masalah tersebut, sehingga muncul upaya-upaya untuk menangani masalah lingkungan. Tulisan ini dikerjakan menggunakan metode sejarah yakni pemilihan topik, heuristik, kritik, interpretasi, dan historiografi serta memanfaatkan sumber primer berupa staatsblad, verslag kolonial, verslag Burgerlijke Openbare Werken (B.O.W.), dan surat kabar sezaman. Penelitian ini memperlihatkan bahwa kemunculan masalah sedimentasi di Selat Madura disebabkan oleh eksploitasi kolonial terhadap hutan di hulu Sungai Bengawan Solo serta masalah siklus banjir dan kekeringan di Gresik, sehingga memunculkan suatu gagasan untuk mengatasi masalah tersebut. Gagasan itu dituangkan dalam perencanaan-perencanaan yang dikerjakan oleh Ledeboer dan Pierson pada paruh kedua abad ke-19 untuk membangun kanal-kanal irigasi dari Ngawi sampai Gresik dengan tujuan guna mengatasi sedimentasi, banjir, dan kekeringan, sehingga muncul proyek irigasi terbesar pada abad ke-19 yakni Solo Vallei Werken.